The Evaluation Of Tibial Torsion Angle After Anterior Cruciate Ligament Reconstruction - Z Işık Solak Görmüş; Mehmet Çelebi; Galip Bilen Kürklü; Faik Özdengül; Ahmet Bayrak; Ali Zergeroğlu; Bülent Işık (Selcuk University, 2020)
The aim of this study is to investigate the effect of anterior cruciate ligament (ACL) reconstruction on tibial torsion angle (TTA) in the operated limb using computed tomography (CT) and physical examination methods and to show the relationship between post-operative muscle strength features and TTA by using isokinetic dynamometer. 21 patients between 18 and 36 years old (25.4±6.8) who underwent ACL reconstruction with hamstring tendon (HT) autograft and then completed the ACL rehabilitation were included in this study. Isokinetic strength measurements were evaluated by Biodex-Multi Joint System-Pro 4 dynamometer. To evaluate TTA; CT, transmalleolar and thigh-foot angle (TFA) measurements were carried out. There was no significant TTA differences between 21 operated and non-operated knees for any method (p gt; 0.05). At the isokinetic evaluation to the extension direction there were a significant differences 60-180º/sec in peak torque value (p=0,0001, p=0,003) and average power value (p=0,004, p=0,002). As the percentage of losses in peak torque value to the flexion direction at velocity of 180 º/sec increases, the CT diagnosed angle difference between both knees increases. (p lt;0,01, r=0,548) As the percentage of losses in average power value to the extension direction at the velocity of 60 º/sec increases, the TFA difference between both knees increases. (p lt;0,01, r=0,563) . The isokinetic evaluation findings show that the strength loss between the knees increases the TTA differences. This finding shows the relationship of post-op rehabilitation with TTA varies and re-injury risk. In the isokinetic evaluation, subjects with high loss of strength in the direction of flexion at 180º/sec velocity had higher TTA differences, so rehabilitation protocols should be also focused on muscle endurance.